The Effect Of The Comparison Of Binders In The Manufacture Of Carp Rolade (Cyprinus Carpio) On The Physical Properties And Consumer Acceptability - Gumilang, Aradea; Kandriasari, Annis; Alsuhendra, Alsuhendra (Sahabat Publikasi, 2024)
This research aims to analyze the effect of binder ratio in the making of carp fish roulade on the physical properties and consumer acceptance. The research was conducted at the Food Processing Laboratory, Department of Culinary Education, Universitas Negeri Jakarta. The research period began in August 2023 and ended in June 2024. The method used in this research was experimental. The research sample used grass carp roulade with a binder ratio between tapioca flour and wheat flour at 1:1, 2:1, and 1:2. The samples were then tested on 30 moderately trained panelists who evaluated overall aspects. Based on the results of statistical hypothesis testing using the Friedman test, it was found that there was no influence of binder ratio on the acceptance of carp fish roulade at ratios of 1:1, 2:1, and 1:2 in terms of skin color before and after frying, filling color before and after frying, fish aroma, spice aroma, taste, and structural compactness. However, one aspect that had an influence was the level of tenderness. Based on the results of statistical hypothesis testing, physical testing using the Kruskal-Wallis test showed that the binder ratio had no significant influence on the physical quality of grass carp roulade in terms of hardness level. The conclusion of this study is that the acceptance of carp fish roulade is recommended at a binder ratio of 1:1 between tapioca flour and wheat flour.